Defense manifestations of enzymatic and non-enzymatic antioxidants in Ricinus communis L. exposed to lead in hydroponics - Kiran Boda Ravi; Prasad M.N.V. (The EuroBiotech Journal, 2019)
Lead (Pb) is a major inorganic pollutant with no biological significance and has been a global concern. Phytotoxicity of lead induces toxic effects by generating reactive oxygen species (ROS), which inhibits most of the cellular processes in plants. Hydro-ponic experiments were performed with Ricinus communis to investigate the toxicity and antioxidant responses by exposing to different concentrations of lead (0, 200 and 400 µM) for 10 days. Pb stress caused a significant increase in electrolyte leakage, non-enzymatic antioxidants (phenols and flavonoids) and a decrease in the elemental profile of the plant. Histochemical visualization clearly indicates the significant increase of H2O2 production in dose-dependent manner under Pb stress. Likewise, an increase in catalase, guaiacol peroxidase and superoxide dismutase activity was also evident. Ascorbate peroxidase and MDAR, on the other hand, responded biphasically to Pb treatments showing a decrease in concentration. The decline in redox ratio GSH/GSSG was imposed by the indirect oxidative stress of Pb. Hence these findings showed the ameliorative potential of R. communis to sustain Pb toxicity under oxidative stress.